Análise do fornecimento de serviços ancilares por um sistema de armazenamento de energia baseado em bateria em uma rede de distribuição - Caldeira, Carolina Albuquerque (2020)
In this work, a battery energy storage system is used along with a bidirectional three-phase converter in order to provide ancillary services to a distribution system, whose voltage and power levels have been adapted in scale from the measured consumption data from the Instituto Federal da Paraíba. Ancillary services include harmonic compensation from non-linear loads connected to the common coupling point, power factor correction and the active power injection by the battery-based energy storage system at peak and off-peak times, in order to minimize demand costs and to reduce power flow. To perform harmonic reduction in the current grid, a proportional-integral control was implemented, in which only the grid current measured was used to perform the control. The battery-based energy storage system’s current control was also performed by the same controller, where it was only necessary to measure the current circulating in the battery, also enabling the control of its state of charge. The energy management, in turn, was carried out according to the load curve analysis of the distribution system under study and the load status of the storage system, where were defined both the peak and off-peak periods in which the the battery would be charged and discharged. The results were obtained through simulations carried out on MATLAB/Simulink® software the experiments were carried out in the Laboratório de Otimização de Sistemas de Energia, which allowed the total harmonic distortion and power factor’s analysis using non-linear load, and the energy analysis using the load curve. Different scenarios that validated the contribution of the proposed system in the provision of ancillary services in the distribution system under study were analyzed.